Students’ motivation and attitude towards the learning of arabic language: A case study of Arabic students in Nigerian universities - Ajape, Kazeem Oluwatoyin; Mamat , Arifin; Abdul Azeez, Yusuf (Econjournals, 2015)
The study of students’ motivation and attitude towards the usage of second language (L2) has recently become an important concept across the disciplines of second language acquisition and communication. This paper highlights the result of the survey questionnaire adopted from Gardner’s (2009) attitude motivation test battery that was administered among 288 Arabic students from six universities in Nigeria. Principal component analysis was carried out to determine the validity of the items in the Nigerian context. 23 out of the 50 items with factor loading <0.40 loaded on four factors with eigenvalue <1.0. Descriptive statistics, Pearson product moment correlation and multiple regression analyses were used to explore the students’ attitude and motivation towards the learning of Arabic language. The four constructs of the questionnaire are: Integrativeness, attitudes toward the learning situation, motivation and instrumentality. The result showed that students have high level of both integrativeness and attitude towards the state of arts of learning, while their level of motivation and instrumentality is very low. In addition to that, there is positive and moderate correlation between integrativenness and attitude towards the state of arts of learning, while the correlation between attitude and motivation is very low. The same thing is applicable to integrativeness and motivation. Instrumentality, however, fails to correlate with any of the factors. The multiple regression analysis showed that attitude toward the state of arts of learning is a good predictor of the students’ integrativeness. In the fi nal analysis, some pedagogical recommendations were put forth in the paper to improve the students’ motivation and positive attitude towards the learning of Arabic language in the Nigerian universities.